Coenzyme Q10 and Neurological Diseases - Gabriele Siciliano; Anna Choub; Michelangelo Mancuso; Daniele Orsucci; Valeria Calsolaro (MDPI AG, 2009)
Coenzyme Q10 (CoQ10, or ubiquinone) is a small electron carrier of the mitochondrial respiratory chain with antioxidant properties. CoQ10 supplementation has been widely used for mitochondrial disorders. The rationale for using CoQ10 is very powerful when this compound is primary decreased because of defective synthesis. Primary CoQ10 deficiency is a treatable condition, so heightened "clinical awareness" about this diagnosis is essential. CoQ10 and its analogue, idebenone, have also been widely used in the treatment of other neurodegenerative disorders. These compounds could potentially play a therapeutic role in Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, Friedreich's ataxia, and other conditions which have been linked to mitochondrial dysfunction. This article reviews the physiological roles of CoQ10, as well as the rationale and the role in clinical practice of CoQ10 supplementation in different neurological diseases, from primary CoQ10 deficiency to neurodegenerative disorders.